Pemberdayaan UMKM Putri Wali sebagai Upaya Peningkatan Ekonomi Masyarakat di Karimunjawa - Nor Hidayati; Harminto Mulyo; Santi Andriyani; Fariza Yulia Kartika Sari; Danang Mahendra; Satria Badruzzaman (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The development of coastal-based MSMEs in Karimunjawa still faces challenges in production management, product quality, and digital marketing, which limit business competitiveness and market expansion. This community service program aimed to improve the production capacity, business management, and digital marketing skills of Putri Wali MSME, a women-based fish processing business in Karimunjawa. The program employed a participatory mentoring approach involving 25 participants through program socialization, training on fish-based product innovation, implementation of Good Manufacturing Practices (GMP) and Occupational Health and Safety (OHS) standards, assistance in smart packaging development, and digital marketing training. The results showed significant improvements in participants’ technical and managerial capacities, including enhanced skills in fish processing, better understanding of hygienic production practices, improved product packaging quality, and increased utilization of digital media for promotion and sales. Evaluation results indicated an average achievement rate of 94.5%, reflecting the effectiveness of the training and mentoring activities. The program contributed to strengthening the sustainability and competitiveness of Putri Wali MSME while supporting the economic empowerment of coastal communities through local resource-based business development.